2021 IEEE International Conference on Pervasive Computing and Communications Workshops and Other Affiliated Events (PerCom Work 2021
DOI: 10.1109/percomworkshops51409.2021.9431034
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Types of Smartphone Usage Sessions from User-App Interactions

Abstract: Understanding how and why people use their smartphones has enabled use cases ranging from correlating behaviour with psychological states through to on-device tasks such as app recommendations. However, being able to effectively and pervasively capture usage behaviour is challenging due to the wide range of functions, apps and interactions that are possible. In this paper, we examine how embedding physical user-app activity (e.g., taps and scrolls) can provide a rich basis for summarising device usage. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…App usage is still strongly linked to the usage context, i.e., prior and posterior used apps. The fact that several apps need to work together to complete a single task causes such correlations [94], [95]. Rahmati et al [96] first demonstrated the app usage dependency of one-nearest prior used apps and found that such a dependency remains relatively constant for one to three months.…”
Section: B App Usage Pattern Discoverymentioning
confidence: 99%
“…App usage is still strongly linked to the usage context, i.e., prior and posterior used apps. The fact that several apps need to work together to complete a single task causes such correlations [94], [95]. Rahmati et al [96] first demonstrated the app usage dependency of one-nearest prior used apps and found that such a dependency remains relatively constant for one to three months.…”
Section: B App Usage Pattern Discoverymentioning
confidence: 99%